THE SCIENCE TEACHING IMPROVEMENT PROGRAM OF THE AMERICAN ASSOCIATION FOR THE ADVANCEMENT OF SCIENCE: AN EVALUATION. - Gustad, John W. (Science Education, 1959)
The article reports that during the years 1956 through 1958, the American Association for the Advancement of Science conducted, as part of its educational program, the Science Teaching Improvement Program (STIP) in the U.S. A major part of the program was the study of the use of science counselors. STIP was set up to work with teachers on the assumption that effects on student learning of science and mathematics. The direct evaluation of STIP were scored by assigning numerical rights to the item responses.